PENGEMBANGAN MEDIA PAPAN PINTAR (PAPIN) MATEMATIKA MATERI PENGURANGAN DIKELAS III SEKOLAH DASAR - Andini Dini; Jayanti Jayanti; Ida Suryani (JS (JURNAL SEKOLAH), 2023)
Abstract: The objectives of this study are to determine: feasibility, practicality, and the effectiveness of media Papan Pintar grade III at SD Negeri 10 Banyuasin I. The research method employed in this study is Research and Development (RnD). The validation of developed media is conducted by media experts and material experts. Additionally, media quality practices are carried out with educators and students. The ADDIE strategy, which has five stages total—analysis, design, development, implementation, or evaluation—was the development method employed in this research. The results from three validators obtained an average score of 92.3%, with a highly satisfactory rating. The practicality assessment, based on questionnaires administered to educators and students shows an average score of 92.2% indicating a highly practical category. The effectiveness assessment, based on the results of pretest and post-test, yielded an overall score of 86.66 in the excellent category. In conclusion, smart board media meets the criteria of being valid, practical, and effective Keyword: Development, Smart board media, Mathematics, Fraction subtraction Abstrak: Tujuan penelitian ini untuk mengetahui: kelayakan, kepraktisan, dan keefektifan dari media papan pintar dikelas III SD Negeri 10 Banyuasin I. Metode yang dipakai pada penelitian ini yaitu Research and Development (RnD). Validasi media yang dikembangkan dilakukan dengan ahli media dan materi. Sedangkan praktik kualitas media dilakukan pada pendidik dan peserta didik. Pada penelitian ini, model pengembangan ADDIE digunakan, yang terdiri dari lima tahap: analisis, desain, pengembangan, pelaksanaan, dan evaluasi. Hasil dari 3 validator dengan perolehan skor rata-rata 92,3% dengan kategori sangat layak. Penilaian kepraktisan melalui angket pendidik memperoleh skor persentase sebesar 92,2% dan peserta didik memperoleh 92,7%% dengan kategori sangat praktis. Penilaian keefektifan dilihat dari hasil protest diperoleh nilai keseluruhan 86,66 dengan kategori sangat baik. Jadi, media papan pintar memenuhi persyaratan valid, praktis, dan efektif.Kata Kunci: Pengembangan, Media Papan Pintar, Matematika, Pengurangan Pecahan